Home–School Interaction: A Vignette Study of Parents' Views on Situations Relevant to Trust. Issue 3 (2nd October 2021) - Bormann, Inka; Killus, Dagmar; Niedlich, Sebastian; Würbel, Iris
Abstract: This paper addresses parental trust in schools (hereafter referred to as "parent trust") in relation to different situations of school-based involvement. More precisely, the study seeks to examine how selected situations of parental school-based involvement (parent-teacher conferences and parents' evenings) are relevant to trust, and what facets of trustworthiness are activated in each situation. In line with the 'comprehensive model of trust' briefly presented in the introductory paper of this special issue, this study aims at interconnecting two elements: "trust among parents and schools" and "promotion of trust" based on perceptions of trustworthiness as antecedents for trusting behavior. Building upon this model and a prior vignette study on parent trust in different situations of school-based involvement, the paper highlights the potential of further theoretical and methodological developments in educational trust research relevant for both research and practice.